Association Between Trait Energy and Fatigue and Aquatic Functional Tests: An Exploratory Study. Issue 1 (1st January 2022) - Boolani, Ali; Allen, Amy; Barrios, Nathalie; Sames, Carol
Abstract : Background: Recent studies have reported energy and fatigue as two separate moods. Interestingly, a recent study reported associations between over-ground functional assessments scores in older adults and feelings of energy, but no significant association between functional status and feelings of fatigue. Purpose: The purpose of this exploratory study is to assess an association between trait mental and physical energy and fatigue and functional assessments in an aquatic setting. Methodlogy: Participants (n=16) in a community aquatic exercise program completed a series of functional assessments; 30-second aquatic sit-to-stand, 7.64-m aquatic walk, and 6-minute walk (6MWT). Assessments for the participants were performed on the first day of aquatics exercise and every 12 weeks thereafter between September 2019 and March 2020. Trait mental and physical energy and fatigue were measured prior to the assessments using the Mental and Physical State and Trait Energy and Fatigue Scales. Using a Wilcoxon rank test, we determined that there were no significant differences between the baseline and 12-week assessments for all trait moods and all functional assessments. Using the Spearman's rho bivariate correlation, we determined that those who reported a higher trait physical energy walked further during the 6MWT and completed the 7.64-m walk quicker. Results: Our findings indicate that the relationship between feelings of physical energy and functional status is also true in an aquatic setting. Conclusion: Clinicians can utilize the findings of our study to design holistic programs that may increase functional status and feelings of physical energy in populations of adults with chronic diseases.